2014
DOI: 10.7314/apjcp.2014.15.1.483
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Cadmium and All Cause, All Cancer and Prostate Cancer Specific Mortalities for Men: an Analysis of National Health and Nutrition Examination Survey (NHANES III) Data

Abstract: Aim: This study employed public use National Health and Nutrition Examination Survey (NHANES III) data to investigate the association between urinary cadmium (UDPSI) and all cause, all cancer and prostate cancer mortalities in men. Patients and Methods: NHANES III household adult, laboratory and mortality data were merged. The sampling weight used was WTPFEX6, with SDPPSU6 applied for the probability sampling unit and SDPSTRA6 to designate the strata for the survey analysis. Results: For prostate cancer death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The studies are listed in chronological order in Table 1. However, out of these seven reports, four were based on the NHANES III population [10,11,13,14], and two studies [9,16] comprised the follow-up of the initial Belgian CadmiBel Study. Of the reports based on the same population, those with the longest follow-up or no restrictions to specific inclusion, e.g., age groups, were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies are listed in chronological order in Table 1. However, out of these seven reports, four were based on the NHANES III population [10,11,13,14], and two studies [9,16] comprised the follow-up of the initial Belgian CadmiBel Study. Of the reports based on the same population, those with the longest follow-up or no restrictions to specific inclusion, e.g., age groups, were included.…”
Section: Resultsmentioning
confidence: 99%
“…The study with the longest follow-up and minimal restrictions was included in the main analysis, and the findings did hold when the estimates of total cancer of Adams et al [10] (average follow-up of 13.6 years) were changed by those of Menke et al [14] (average follow-up of 9.0 years). The NHANES III study published by Cheung et al [11] did not take the prospective nature of the data into account and was therefore not considered in the sensitivity analysis. An additional study within the NHANES III study population specifically addressed the question whether cadmium-zinc interactions might modify the risk of cadmium-induced cancers.…”
Section: Relaɵve Risk (95% Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium is able to produce malignant tumors in multiple organs following loge term and chronic exposure (Waalkes et al, 1999a(Waalkes et al, , 1999b. Besides experimental studies, epidemiological studies have also confirmed the potential cadmium carcinogenicity (Joseph, 2009;Cobanoglu et al, 2010;Rahim et al, 2013;Cheung et al, 2014).…”
Section: Cadmium and Cancermentioning
confidence: 91%
“…Varios estudios epidemiológicos [13][14][15][16][17][18][19][20][21] investigan la asociación entre la exposición ocupacional al cadmio y el desarrollo de neoplasia de próstata, sin embargo se han presentado hallazgos inconsistentes. Algunos estudios han demostrado una relación significativa [13][14][15][16] , otros una asociación débil 17,18 , mientras que otros, por el contrario, no demostraron ninguna asociación 19,20 (IARC) reporta en su informe de 2018 resultados contradictorios sobre la asociación entre la exposición al cadmio en el medio laboral y el desarrollo de neoplasias de próstata. Los incrementos que se observaron en unos primeros estudios de cohortes no pudieron confirmarse en estudios posteriores.…”
Section: Introductionunclassified